Membangun Ide Kreatif - Halawa, Irwan; Effendy, Erwan; Munthe, Lidia H; Pikardi, Rezi (Ikatan Da'i Indonesia, 2023)
Building creative ideas is a very important educational and life demand at this time. Creativity will produce new innovations in this life. These creative individuals and organizations are always needed by their environment because they can meet the continuous needs of the environment and are able to survive until now with the development of this era. and tight. This very important creative potential is basically owned by every human being, that humans have characteristics by experts who are often classified as creative individual characteristics, for example: great curiosity, likes to ask questions, high imagination, dare to take responsibility for risks, happy of something new, and so on. Thus, the factors of parents, teachers in schools, and the environment are important factors that greatly influence the development of creativity. This research is a descriptive research, which describes and explains all the things studied, namely how to build creative ideas. The methodology of this research is documentation, which is the source of data obtained from agencies or books (documents) related to this research problem. By creating this creative idea, we can come up with new works. With the development of an increasingly advanced era, we can use this technological tool in building new ideas. This is done in order to attract people in us to make or build something, as for other reasons so they don't get bored. By building creative ideas, you can solve problems and make things successful.